2016
DOI: 10.1055/s-0035-1562794
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Cross-Dehydrogenative Coupling of Triazines with 5,7-Dihydroxycoumarins

Abstract: A new method for the direct metal-free C-H functionalization of electron-deficient triazines with fragments of naturally occurring and synthetic 5,7-dihydroxycoumarins is reported. It has been found that the reaction of 5,7-dihydroxycoumarins with triazines proceeds under mild conditions, showing a high chemo-and regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…The dihedral angle between the two units was found to be 127.28(4)°and 129.7(1)°, respectively. All bond parameters are comparable to closely related compounds in literature [15][16][17][18][19][20][21]. Neighbouring molecules are joined together via classical intermolecular O-H• • • O hydrogen bonds between the hydroxyl and carbonyl groups.…”
Section: Commentsupporting
confidence: 61%
“…The dihedral angle between the two units was found to be 127.28(4)°and 129.7(1)°, respectively. All bond parameters are comparable to closely related compounds in literature [15][16][17][18][19][20][21]. Neighbouring molecules are joined together via classical intermolecular O-H• • • O hydrogen bonds between the hydroxyl and carbonyl groups.…”
Section: Commentsupporting
confidence: 61%
“…In a continuation of our research on CDC reactions in triazines [ 54 , 67 ] and diazines [ 68 ], herein, we are pleased to report an unusual synthesis of benzofuro-fused 1,2,4-triazines via the sequence of C-C/C-O CDC reactions of 1,2,4-triazines with 2-naphthols or phenols ( Scheme 1 d). The reaction proceeded through the formation of 1,4-dihydrotriazine, followed by oxidative cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of pteridin-4-one (R=H), the oxidative coupling products were obtained in moderate yields via a one-step reaction involving TFA. [91] Khalymbadzha et al [92] showed that 5,7-dihydroxycoumarins can undergo nucleophilic addition to sand as-triazines in the same manner as diazines [91] to form stable σ H -adducts in yields of up to 97%. p-Chloranil enabled the aromatisation of the dihydrotriazine σ H -adducts, affording the oxidative coupling products in good yields.…”
Section: Cdc Reaction Of Phenols With π-Deficient Heterocyclesmentioning
confidence: 99%
“…Khalymbadzha et al [92] . showed that 5,7‐dihydroxycoumarins can undergo nucleophilic addition to s ‐ and as ‐triazines in the same manner as diazines [91] to form stable σ H ‐adducts in yields of up to 97%.…”
Section: Cdc Reaction Of Phenols With π‐Deficient Heterocyclesmentioning
confidence: 99%